2018
DOI: 10.1002/tqem.21595
|View full text |Cite
|
Sign up to set email alerts
|

The influence of green energy investments on environmental quality in OECD countries

Abstract: This empirical study analyzes the relationship between green energy investments on environmental quality in Organisation for Economic Co‐operation and Development (OECD) countries from 2000 to 2014. Environmental quality was disaggregated into five widely known proxies: carbon emissions, greenhouse gases, carbon monoxide, sulfur oxides, and nitrogen oxides. On one hand, using the system‐Generalized Method of Moments estimator, the results of this paper demonstrate that renewable energy investments, primary ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…This diagnosis implies that when past greenhouse gas emissions in the EU economies rise then they will also stimulate current emission levels. This is confirmed by continued increase in emissions globally [60,75] which require to be lowered. Secondly, the total environmental tax shows a positive and highly significant association with greenhouse gas emissions.…”
Section: Panel Unit Root Test Analysismentioning
confidence: 89%
See 1 more Smart Citation
“…This diagnosis implies that when past greenhouse gas emissions in the EU economies rise then they will also stimulate current emission levels. This is confirmed by continued increase in emissions globally [60,75] which require to be lowered. Secondly, the total environmental tax shows a positive and highly significant association with greenhouse gas emissions.…”
Section: Panel Unit Root Test Analysismentioning
confidence: 89%
“…Green Research and Development is defined as new innovations introduced to minimise emissions and climate change in the European Union [60]. A positive relationship between Green Research and Development and environment sustainability is expected while an inverse relationship on greenhouse gas emission is expected.…”
Section: Data and Research Methodologymentioning
confidence: 99%
“…Their empirical results also indicated that a rise in public budget for energy research & development expenses leads to improve environmental quality by declining CO 2 emissions. Similarly, Ganda (2018) examined the effect of green energy investment on carbon emissions in the case of OECD countries for the period of 2000-2014. They noted that investment in green energy i.e.…”
Section: III Public-private Partnerships Investment In Energy-emissimentioning
confidence: 99%
“…The EMT can occur via incremental improvements (cleaner technologies) or through radical innovation (clean technologies) (Janicke, ). These improvements affect different dimensions, such as the efficient use of materials or space, energy (Ganda, ), transport and logistics systems, or risk intensity regarding plants, substances, and products. Several sectors are engaged in the search for better alternatives to waste management, such as in the electrical and electronic equipment sector (Merino‐Saum, Baldi, Gunderson, & Oberle, ), remote campsites to reduce litter deposited in landfills (Isola et al., ), in agrobusiness (Sehnem et al., ), household food waste (Schmidt & Mathies, ), the copper sector (Wang et al., ), and the ferronickel sector (Xi et al., ), among many others.…”
Section: The Emtmentioning
confidence: 99%